INTERACTION OF AROMATIC CYTOKININS WITH HUMAN LIVER MICROSOMAL CYTOCHROMES P450 - Anzenbacherová, Eva; Janalík, Jakub; Popa, Igor; Strnad, Miroslav; Anzenbacher, Pavel (Biomedical papers, 2005)
Aromatic cytokinins (ortho-topolin riboside, 6-benzylaminopurine riboside and 6-(2-hydroxy-3-methoxybenzyla mino)purine riboside) were tested for their possible interaction with human liver microsomal cytochromes P450 by absorption difference spectroscopy. All three compounds were shown to bind to the CYP enzymes producing a high to low spin shift of the heme iron yielding a Soret absorption band shift to approximately 425 nm. As this type of spectral change means that the substance is able to bind directly to the heme iron, the results obtained open the possibility of an interaction of these compounds with metabolism of other drugs or, in general, with other substrates of cytochromes P450.
Keywords: Cytokinins/Cyclin dependent kinase inhibitor/Cytochrome P450/CYP/Human microsomes